The impact of air pollution on career changes among Chinese workers - Jinhuang Chen; Xuewen Long (Scientific Reports)
Abstract The influence exerted by air pollution on interregional workforce migration has garnered considerable attention in ecological economics over time; however, relatively scant consideration has been given to its effects on occupational transition dynamics. This study presents an empirical examination of the influence of air pollution on job changes among the working population and seeks to understand the underlying causal mechanisms. By merging detailed micro-level survey data with regional Fine particulate matter (PM2.5) data from Chinese counties spanning the years 1997 to 2015, we have constructed an extensive database to support our analysis. The study revealed that air pollution has a significant negative impact on the likelihood of career switching. Mechanistic analysis indicates that changes in wage compensation, as well as declines in health status, serve as the primary pathways through which air pollution exerts its influence. To reduce the welfare loss caused by air pollution, it is crucial to prioritize the welfare benefits and health conditions of the labor force.